-7x+37=-3(1+5x)

Simple and best practice solution for -7x+37=-3(1+5x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+37=-3(1+5x) equation:


Simplifying
-7x + 37 = -3(1 + 5x)

Reorder the terms:
37 + -7x = -3(1 + 5x)
37 + -7x = (1 * -3 + 5x * -3)
37 + -7x = (-3 + -15x)

Solving
37 + -7x = -3 + -15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15x' to each side of the equation.
37 + -7x + 15x = -3 + -15x + 15x

Combine like terms: -7x + 15x = 8x
37 + 8x = -3 + -15x + 15x

Combine like terms: -15x + 15x = 0
37 + 8x = -3 + 0
37 + 8x = -3

Add '-37' to each side of the equation.
37 + -37 + 8x = -3 + -37

Combine like terms: 37 + -37 = 0
0 + 8x = -3 + -37
8x = -3 + -37

Combine like terms: -3 + -37 = -40
8x = -40

Divide each side by '8'.
x = -5

Simplifying
x = -5

See similar equations:

| 7(8-3x)=182 | | 0.19y+0.07(y+4000)=1060 | | 5x-14=4(2x+1) | | x-4/3+4/3=-x/5 | | 2-3x=62 | | 8x^2+28x=-24 | | 8y-6=2y+8 | | 26/57=849/5x | | 5x/6-(3-x)/8=4x+3/12 | | 2xsquared+12.5=0 | | 1=2-3v+2v | | 33=-8x-31 | | 6(2w+v)-4(2v+1w)=0 | | -3/8p=-9 | | .6x^2=3.6x+.6 | | 5x+3=4x-14 | | 1/2(3t-7)=t/4+7/4 | | -(2x-5)-(2x-6)+3=-4(x-1)-(3x+5)+3 | | 6p+4p+.75+3p= | | -73+8x=71 | | 3(m-z)+5(2m-z)=0 | | 7p^2=-18p-8 | | 12x+15(312-x)=13*312 | | 33x^2+39x=0 | | -86=-2(3n+1)-6n | | -83=10x+97 | | 7y+(5y+5)= | | 8x+5-6(x+1)=7x+3 | | 2y+3(y-9)=-3(3y-18)-y | | -7(1+3x)=161 | | 1=5p-2-2 | | (c)8-10=3c+5 |

Equations solver categories